Decentralizacija evropskega avantgardizma in omrežje jugoslovanske avantgarde - Pranjić, Kristina (Amfiteater (Ljubljana), 2025)
The article analyses the decentralisation of the European avant-garde canon by focusing on the Yugoslav avant-garde, presenting it as a polycentric and rhizomatic network of artistic practices. It introduces the transnational and network approaches and an interdisciplinary methodological framework that have contributed to reshaping the understanding of avant-garde movements. Central attention is given to key concepts and theories that support a rhizomatic approach to researching the avant-garde, with theoretical foundations highlighted through examples of Yugoslav Dadaism, Zenitism and Constructivism. Particular emphasis is placed on the concepts of “barbarogenius” and the “Balkanisation of Europe” as strategies of subverting imperial discourses, which are compared to the figure of the “cannibal” in the work of Latin American avant-gardist Oswald de Andrade. The article argues for a transnational reading of marginal avant-gardes, revealing global networks of resistance against Eurocentric narratives of modernity. By presenting the Yugoslav avant-garde as a dynamic network and grounding the network approach, the article contributes to broadening the understanding of the avant-garde beyond a Eurocentric perspective. It opens space for further research into marginalised or minor artistic practices, pluralising the image of European modernity.
Keywords: historical avant-garde; horizontal art history; horizontalna zgodovina umetnosti; jugoslovanska avantgarda; network approach; omrežni pristop; rhizomatic phenomenon; rizomotski fenomen; Yugoslav avant-garde; zgodovinska avantgarda